HUBUNGAN DAYA LEDAK OTOT LENGAN DAN BAHU DENGAN KETEPATAN SMASH ATLIT PUTRA PB. SILVA PEKANBARU - Satrio Mandala Putro; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The aim of the research was to get the correlation of explosive power relationship of the arm and shoulder muscles with the accuracy of the male athlete smash at PB. Silva Pekanbaru. The forms of this research was the correlation study, the population in this study was Putra PB Putra Pekanbaru and the sample in this study was 6 atlete. While the sample tecnique used is total sampling (saturated sample), where all the population as the sample. So, the sample in this study amounted to 6 students. After that, the data is processed with statistics, normality test with liliefors test and correlation at significant level α (0,05). The analysis in the calculation of the correlation between X and Y, where rtable at significant level α (0,05) = 0,811 means rresult (0,847) > (0,811), which means the hypothesis is accepted and there is a meaningful correlation with strong interpretation between exxplosive power relationship of the arm and shoulder muscles with the accuracy of the male athlete smash at PB. Silva Pekanbaru. Than it can be concluded that the correlation between explosive power relationship of the arm and shoulder muscles with the accuracy of the male athlete smash at PB. Silva Pekanbaru are significantKeywords: Explosive power relationship of the arm and shoulder muscles,the accuracy.